The Calculation of Firing Safety Zone Based on Ballistic Curve Model. (September 2020) - Meng, Xianyu; Cui, Yanping; Gao, Juan; Cai, Xiaoyan
Abstract: This paper discusses the determination of the safety zone of artillery fire drill. For the convenience of research, the safety zone is divided into absolute safety zone and relative safety zone. The ballistic curve model starts from the analysis of the trajectory of the projectile, through the analysis of the forces on the flying projectile, using Newton's second law and the differential equations, the ballistic curve model describing the trajectory of the projectile is established. After that, the trajectory curve parameters of given launch angle are calculated by using MATLAB software, and the farthest range of projectile is obtained. According to the relationship between the range and the angle of the projectile in the ballistic curve model, the angle of the projectile can be obtained, and then combined with the upper limit of the angle of the projectile launching error, the range of the projectile falling point can be obtained.